An Overview of Functional Gradient Biomaterials Manufacturing Process of Implants Types - Khalil, Nawzad K.; Takhakh, Ayad, M.; Ali, Abdalla Abdul-Hay (Al-Nahrain Journal for Engineering Sciences, 2024)
Functionally graded material is one of the promising sectors of the material since because of the great ability to control with required product properties could be strongly used in biomedical applications exclusively in the implants sector, this review paper demonstrates briefly about the most prominent known manufacturing methods and focusing on the implants coated by FGM layer manufactured by using EPD method because the EPD has significant properties it could produce FGM layer in the Room temperature without depending on chemical reactions or heat adding, Biomedical application need highly accuracy when we deal with material that directly contact with human tissue because the heat effect could be change the biocompatibility properties and also the chemical reactions could make toxic effect on the produced implants, All these reasons make the EPD one of the favorable method for the FGM coated Implants. this paper will summarise and give the Gide line for the researcher about the most important substrate and suspension materials used in the EPD method and its application.